Alikhan Bokeikhan’s Literary Preservation of Kazakh Identity Against Colonial Ideology - Osken, Assem (Archīum Ateneo, 2024)
In the history of the world, imperialist countries happened to pursue a policy of colonization to destroy ethnic consciousness, culture, language, and knowledge. This article comprehensively analyzes the literary works of the national leader Alikhan Bokeikhan, who opposed the policy of the Russian Empire in the 19th century and its successor, the Soviet government in the 20th century that was aimed at gradually destroying the Kazakh people as a distinct group of Kazakh people. The research shows that literary translations, critical articles, and folklore samples of Bokeikhan greatly contributed to the preservation of Kazakh language, religion, culture, national education and literary and cultural heritage, as well as the revival of Kazakh identity and preservation of “national memory.” The Soviet government banned using the works of Bokeikhan and other Alash followers, a group of Kazakh intellectuals whose democratic and progressive views contributed to the development of Kazakh culture, literature and science, and even mentioning their names; therefore, those works began to be studied only after Kazakhstan gained its independence in 1991. Their works are among the most valuable national cultural heritage for the Kazakh people today since every cultural and political initiative of Alash intellectuals is fundamental work done to modernize the consciousness of the Kazakh people.